Synthesis of New Annulated Pyrazinothienotriazolopyrimidinones and Triazolylthienopyrazines - Campos, Joana F.; Queiroz, Maria-João R. P.; Berteina-Raboin, Sabine (Synthesis, 2018)
New pyrazino[2′,3′:4,5]thieno[2,3-e][1,2,3]triazolo[1,5-a]-pyrimidin-5(4H)-ones were synthesized in an efficient, fast, and mild one-pot procedure from methyl 7-azidothieno[2,3-b]pyrazine-6-carboxylate. From the latter, some triazolothieno[2,3-b]pyrazine-6-carboxylates were also obtained with total regioselectivity by [2+3] cycloaddition with alkynes without any metal catalyst.
Keywords: heterocycle; pyrazinothienopyrimidines; thienopyrazines; cycloaddition; one-pot cyclizations